The Use of Electronic Money (E-Money) From an Islamic Economics Perspective: A Qualitative Descriptive Review of Compliance, Challenges, And Social-Economic Implications - Barokatut Toyibah (SHACRAL: Shari'ah Economics Review Journal, 2024)
The rapid advancement of digital technology has significantly transformed payment systems, with electronic money (e-money) emerging as a dominant non-cash transaction instrument in many economies, including Indonesia. As part of the broader digital financial ecosystem, e-money has been widely adopted due to its efficiency, convenience, and integration with mobile platforms. According to data from Bank Indonesia, the volume and value of e-money transactions have increased substantially over recent years, reflecting a structural shift in consumer payment behavior toward cashless transactions (Bank Indonesia, 2023; Bank Indonesia, 2024; World Bank, 2023). Despite these developments, the widespread use of e-money raises important questions within the framework of Islamic economics, particularly regarding its compliance with Sharia principles such as the prohibition of riba (interest), gharar (excessive uncertainty), and maysir (speculation). This study adopts a qualitative descriptive approach based on a comprehensive literature review, without relying on primary empirical data. The research aims to examine how e-money is conceptualized, regulated, and practiced from an Islamic economic perspective, drawing on scholarly works, regulatory documents, and institutional reports at both national and international levels. The findings indicate that e-money is generally considered permissible (mubah) under Islamic law, provided that its operational mechanisms comply with Sharia principles and align with the objectives of Islamic law (maqāṣid al-sharīʿah), particularly the protection of wealth (ḥifẓ al-māl) and the promotion of public welfare (maṣlaḥah) (Syamsuri et al., 2020; Baso et al., 2023; Hassan et al., 2021). However, the study also identifies several challenges, including limited public understanding of Sharia-compliant e-money, the dominance of conventional providers without explicit Sharia certification, and regulatory gaps in ensuring consistent Sharia governance. These challenges highlight the need for stronger regulatory coordination, enhanced Islamic financial literacy, and deeper academic engagement with digital payment innovations. Overall, this study contributes to the growing discourse on Islamic digital finance by offering a structured conceptual analysis of e-money within the Islamic economic paradigm.